Safety Concerns on the Use of Compressed Natural Gas (CNG) in the Nigerian Automobile Industry - Agbonyososo D. OKPERE; Kenneth K. ADAMA (FUDMA Journal of Engineering and Technology, 2026)
Compressed natural gas (CNG) offers Nigeria’s automotive industry a cleaner and cost-effective alternative fuel. However, safety concerns has continued to hinder its full adaption since its launch in Nigeria in 2023 by the presidential initiative on compressed natural gas utilization. This study assessed the safety concerns associated with CNG-usage in the Nigerian automobile industry through the adaptation of a descriptive research design methodology involving surveys, policy reviews and international case studies. The study revealed that about 50.6 % of the respondent view CNG vehicles as safe from the sampled population with key concerns on explosion risks (48.1 %), capacity of technicians (40.3 %) and refueling infrastructure inadequacy (35.1 %). Furthermore, overlaps in regulatory agencies in the sectors such as the standard organization of Nigeria (SON), and Department of Petroleum Resources (DPR), coupled with low public awareness with about 26.0 % been unaware of safety standards exacerbated associated risks was revealed. The study highlighted the need for unified regulations, enhanced capacity of technicians through constant trainings, expanded infrastructure and sustained public awareness campaigns, implementing standards like ISO 11439 and establishing a CNG safety task force would ensure the safe adoption of CNG in the Nigerian automobile industry, boost public confidence and support Nigeria’s transition to sustainable transportation.